ANALISIS LAJU PENUAAN ISOLASI KERTAS MENGGUNAKAN ESTER BASED OIL PADA TRANSFORMATOR RAMAH LINGKUNGAN - Agung Sukma Hardana; Syamsir Abduh; Tyas Kartika Sari (Jetri : Jurnal Ilmiah Teknik Elektro, 2022)
Transformer oil function as the cooling medium and electrical insulation component in power transformer. It has to follow minimum acceptable criteria as regulated in international standard, as IEC standard. In general, the most transformer oil used in power transformer is mineral oil. Due to the sustainability of the raw material and the bad impact to the environment, it is important to find the new transformer oil as alternative to the mineral oil. The intention of this reseeach is to study the characteristic of the ester based oil: breakdown voltage, tangen delta and color. Analyis was performed by comparing the characteristic from both oils, and reviewed the parameters against the minimum criteria as required by IEC standard. Based on the analysis, ester based oil fulfill criteria and can be used for the transformer oil. Furthermore, based on the degree polymerization test result from the paper insulation immersed in both oils, it can be concluded that the insulation paper immersed in ester based oil has slower aging rate than insulation paper immersed in mineral oil.